Aadhaar - Shainesh, G., (SAGE Knowledge. Cases., 2018)
Aadhaar, India's system for giving every resident a unique twelve-digit identification number, represented an astounding achievement. In 2010, Indian officials began registration by collecting biometric data (photographs, fingerprints, and iris scans). By 2017 over 1.1 billion people were registered.By 2017, over 95% of India's population had Aadhaar numbers. Officials estimated that social welfare programs were saving billions of dollars. Banks and mobile phone companies were streamlining account set-up and expanding to new customers. Entrepreneurs and established businesses sought new uses for Aadhaar. However, as Aadhaar expanded, there were concerns. Privacy advocates objected to Aadhaar's sweeping role in society and filed a series of court cases about collecting and storing sensitive data. India had few laws concerning data privacy, and many were looking for possible models. Government efforts to link Aadhaar to taxpayer identification and bank account numbers were receiving stiff resistance. Observers wondered how these challenges would shape the way that Aadhaar would be used by both the private and governmental sector.